Overexpression and DNA-binding properties of the mer-encoded regulatory protein from plasmid NR1 (Tn21). - Heltzel, A (1987)
In plasmid NR1 the expression of genes involved in mercury resistance (Tn21) is regulated by the trans-acting product of the merR gene. An in vivo T7 RNA polymerase-promoter overexpression system was used to detect a protein of approximately 16,000 daltons encoded by the merR reading frame. Overexpressed MerR constituted about 5% of labeled proteins. An in vitro MerR-mer-op (mer-op is the mer operator and promoter region) gel electrophoresis binding assay established that the binding site for MerR was located between the putative -35 and -10 sequences of the promoter for the mer structural genes. A nonsense mutation in the carboxyl half of MerR resulted in the loss of biological function and the loss of in vitro mer-op binding properties.